Epigenetic potential of resveratrol and analogs in preclinical models of prostate cancer. (27th July 2015) - Kumar, Avinash; Dhar, Swati; Rimando, Agnes M.; Lage, Janice M.; Lewin, Jack R.; Zhang, Xu; Levenson, Anait S.
Abstract : Lifestyle, particularly diet, is a risk factor for prostate cancer. Dietary polyphenols such as resveratrol possess anticancer properties and therefore have chemopreventive and therapeutic potential. Resveratrol has pleiotropic effects, exerting its biological activity through multiple pathways and targets, including those associated with cancer. Numerous studies have demonstrated the anticancer effects of resveratrol and, to a lesser extent, its analogs, in tissue culture, while in vivo observations are limited. Here, we provide a concise summary of our results on epigenetic mechanisms of resveratrol and analogs mediated through regulation of chromatin modifier metastasis‐associated protein 1 (MTA1) and microRNAs (miRNAs), and highlight the anticancer effects of these compounds in preclinical models of prostate cancer. We suggest that the identified stilbene responsive mechanism–based biomarkers, such as MTA1 and oncogenic miRNAs, may become indicative of treatment efficacy in prostate cancer. Resveratrol analogs with better bioavailability, conferring superior pharmacological potencies and greater anticancer effects, may become stronger candidates for clinical development.